STRATEGI PENGEMBANGAN PEMASARAN MAKANAN KHAS BENGKULU PADA SENTRA OLEH-OLEH ANGGUT KOTA BENGKULU: APLIKASI AHP DAN SWOT - Hutagalung, Chresy Novralina; Nusril, Nusril; Adiprasetyo, Teguh (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2012)
The aim for this research is to know the marketing development strategic of traditional meal in Centra traditional food Anggut Bengkulu City using Analytical Hierarchy Process (AHP) method dan SWOT analysis. The samples are Cita Rasa, Kueku Yovita and Arzel. To find the priority factor from each marketing mix used Analytical Hierarchy Process (AHP) method. This research showed that the priority factor from product mix is the hygiene product (0,1222). The priority factor from price mix is the value for money (0,2025). The priority factor from promotion mix is positioning the local product (0,1539). The priority factor from place mix is market location position (0,1841). The internal and external environment is used in SWOT analysis matriks. The Cita Rasa marketing development strategics are giving incentive price for consumers, market expansion, keep and maintain quality, taste and locallity product, and decorate the layout on the attractive display. The Kueku Yovita marketing development strategics are increase the promotion and advertising, giving incentive price for consumer, market expansion, and decorate the layout on the attractive display. The Arzel marketing development strategics are increase the promotion and advertising, giving incentive price for consumer, market expansion, increase the quality, hygiene and taste product, and decorate the layout on the attractive display.